Imagens da pré-história: as mãos na pintura rupestre no alto sertão baiano - Rabello, Angela Maria Camardella (1997)
This thesis considers rock painting as a language and thus a form of social communication and signification in the context of the pre-writing cultures that inhabited the high sertão of Bahia State, in Brazil. It describes a study in the anthropology of art seeking to explain culture on the basis of esthetic phenomena. Since 1983, as an archeologist with the National Museum (a unit of Rio de Janeiro Federal University) and member of the team of Project Central under the orientation of Professor Maria da Conceição Beltrão, I have given especial attention to records of hands in the universe of rock signs. The notions of "total social fact" (Marcel Mauss), "science of the concrete" (Claude Lévi-Strauss) and "graphic symbolism" (André Leroi-Gourhan) constitute the theoretical principles underpinning this study. The sample comprises the Chico Eduardo, Búzios, Dois Irmãos and do Riachão archeological sites, known locally as "tocas” (caves), plus the Pequeno cave and Riacho Largo canyon, all located in the northeastern slopes of the Chapada Diamantina uplands. The local vegetation, typical of the semi-arid northeast sertão, is caating scrub. The monograph also includes a review of texts on the prehistory of Bahia State written by Theodoro Sampaio, Carlos Ott, Valentin Calderón, Pedro Ignacio Schmitz and Maria Beltrão. I offer a descriptive table of "traditions" and “styles" of rock paintings in Bahia and establish correlations with other states in Brazil. The processes of the settlement and geographical displacement of Bahia’s indigenous peoples are illustrated on maps also showing the prehistoric settlements, indigenous groups from the 16th to the 19th century and the territories of contemporary indigenous groups. In seeking a theory of images, I found in the semiotics of Charles Sanders Peirce a model for investigating the dynamics of the effect of "hand-on-stone" signs on the mind of the interpreter (the past culture). Bringing an "archeological imagination" (Luiz Felipe Flores) to bear, to interpretation that I offer for the culture that produced the “hand-on-stone" incorporates information obtained by a semiotics-based analysis, as well as archeological and ethnographic data.